The evolution of parental cooperation in birds - Remeš, Vladimír; Freckleton, Robert P; Tökölyi, Jácint; Liker, András; Székely, Tamás (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Parental care is one of the most variable social behaviors and it is an excellent model system to understand cooperation between unrelated individuals. Three major hypotheses have been proposed to explain the extent of parental cooperation: sexual selection, social environment, and environmental harshness. Using the most comprehensive dataset on parental care that includes 659 bird species from 113 families covering both uniparental and biparental taxa, we show that the degree of parental cooperation is associated with both sexual selection and social environment. Consistent with recent theoretical models parental cooperation decreases with the intensity of sexual selection and with skewed adult sex ratios. These effects are additive and robust to the influence of life-history variables. However, parental cooperation is unrelated to environmental factors (measured at the scale of whole species ranges) as indicated by a lack of consistent relationship with ambient temperature, rainfall or their fluctuations within and between years. These results highlight the significance of social effects for parental cooperation and suggest that several parental strategies may coexist in a given set of ambient environment.
Keywords: ptáci; Birds; druhová specificita; Phylogeny; Biological Evolution; Female; zvířata; behavior; Sex Ratio; sexual selection; ženské pohlaví; parental care; Male; fylogeneze; biologická evoluce; Species Specificity; poměr pohlaví; Animals; climate; mužské pohlaví; sex ratio